Application of Alternative Energy Sources as A Sustainable Strategy in Sri Lanka: Cases Review - Ratnasingam, Ganeshwaran (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
This research aims to assess the feasibility and applicability of sustainable energy models for Sri Lanka by analyzing three successful case studies from different regions. The methodology involves examining solar PV installations in Iran's Lut Desert, rooftop solar PV projects in India, and combining floating solar panels with hydropower in various countries. The findings indicate that each case study offers unique advantages, with the potential for solar PV projects to address urban energy needs in Sri Lanka. The twinning of floating solar panels with hydropower also shows promise, leveraging the country's water resources. This study highlights the importance of tailored approaches and diversified sustainable energy projects for Sri Lanka, considering its distinctive characteristics. Keywords: Alternative Energy Sources in Sri Lanka; Rooftop Solar Power; Green and Sustainable Energy; Rent-a-Roof Project; Twinning Floating Solar and Hydropower